The Role of CXC Chemokines in Cardiovascular Diseases - Xiyi Lu; Zhen Wang; Di Ye; Yongqi Feng; Menglin Liu; Yao Xu; Menglong Wang; Jishou Zhang; Jianfang Liu; Mengmeng Zhao; Shuwan Xu; Jing Ye; et al. (Frontiers Media S.A., 2022)
Cardiovascular disease (CVD) is a class of diseases with high disability and mortality rates. In the elderly population, the incidence of cardiovascular disease is increasing annually. Between 1990 and 2016, the age-standardised prevalence of CVD in China significantly increased by 14.7%, and the number of cardiovascular disease deaths increased from 2.51 million to 3.97 million. Much research has indicated that cardiovascular disease is closely related to inflammation, immunity, injury and repair. Chemokines, which induce directed chemotaxis of reactive cells, are divided into four subfamilies: CXC, CC, CX3C, and XC. As cytokines, CXC chemokines are similarly involved in inflammation, immunity, injury, and repair and play a role in many cardiovascular diseases, such as atherosclerosis, myocardial infarction, cardiac ischaemia-reperfusion injury, hypertension, aortic aneurysm, cardiac fibrosis, postcardiac rejection, and atrial fibrillation. Here, we explored the relationship between the chemokine CXC subset and cardiovascular disease and its mechanism of action with the goal of further understanding the onset of cardiovascular disease.